Kali macrura Parr 1933 - Melo, Marcelo R. S. (Zenodo, 2008)
Kali macrura (Parr 1933) (Figs. 1 D, 6, and 7; Tables 1, 7, and 8) Hemicyclodon macrurus Parr 1933 [original description; type locality, off Acklins Islands, Bahamas, 22°31’15” N, 74°26’20” W, 10000 ft. (3048 m) of wire, 30–III–1927, R/V Pawnee holotype YPM 2739]. Kali macrurus Johnson 1969: 589, figure 1 [revision of the genus and key to the species]. Kali macrura Johnson and Cohen 1974: 39 –41 [revision of the genus, diagnosis and brief description]; Johnson and Keene 1986: 733 –734, figure 228.7 [key to the species]; Johnson and Keene 1990: 902 [record of eastern tropical Atlantic species]; McEachran and Sutton 2003: 1742 –1743 [list of Atlantic species]; Moore et al. 2003: 227 [checklist of deep-sea fishes from off New England, Western North Atlantic]; Hardy 2005: 1912 [identification of larvae]; Hardy 2007: 1902 [identification of larvae]; Smith (in press) [key to species]. Material examined. 26 specimens, including holotype. Atlantic, Slope Water: MCZ 165931, 1, 118.03 mm, 39°47’ N, 66°55’ W, 0–2208 m, 18–VI–2006, R/V Delaware II. Florida Straits: YMP 2739, holotype, 114.3 mm, 22°31’ N, 74°26’ W, 30–III–1927, R/V Pawnee UF 146164, 1, 112.3 mm, 2450 m, 24–VII–1971, R/V Pillsbury . Amazonian Province: MCZ 60723, 1, 72.5 mm, 9°21’ N, 43°09’ W, 2500 m, 27–VII–1983, R/V Columbus Iselin . South Atlantic Subtropical: SIO 63–542–60, 1 113.8 mm, 31°09.0’ S, 00°45.5’ E, 0–2200 m, 9–VI–1963, R/V Argo UW 21247, 1, 117.0 mm (cs), 27°14’ S, 2°56’ W, 1900–2000 m, 1–IV–1971, R/V Walther Herwig . Guinean Province: USNM 207615, 1, 101.8 mm, 15°45’ S, 6°06’ W, 0–1900 m, 5–VI– 1971, R/V Walther Herwig . Indian: USMN 207608, 1, 111.3 mm, 24°03’ S, 65°00’ E, 3500 m, 25–VI–1964, R/V Anton Bruun BMNH 1988.2.25.7–8, 2, 125.5– 130.4 mm, 31°55’ S, 55°06’ E, 0–930 m, 29–IV–1936, R.R.S. Discovery II . Eastern Pacific: LACM 30428, 1, 105.5 mm, 33°00’ N, 119°00’ W [coordinates inferred], 17/ 18–III–1969, R/V Ve le ro LACM 30040–11, 1, 121.4 mm, 22°00’ N, 107°00’ W [coordinates inferred], 12–XI–1967, R/V Vel ero Pacific, ...